2019
DOI: 10.3390/cryst9120618
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Non-Linear to Linear Shift in Magnetoresistance of Amorphous Carbon Films

Abstract: Non-linear to linear negative magnetoresistance (MR) was studied under the magnetic field ranging from −7 T to 7 T with a change in measurement temperature from 2 K to 300 K. Under the magnetic field of 7 T, a maximum MR magnitude of 8.2% was observed at 2 K. The chemical vapor deposition technique was adopted to synthesize the amorphous carbon thin films. Non-saturated and non-linear negative MR was observed for the lower temperatures, while 10 K was observed as transition temperature. Afterwards, the more li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…As the carbon material consisted of a majority of sp 2 clusters and are good conductors, while the carbon material consisted of a majority of sp 3 clusters and are not good conductors [26], the samples with a larger C(sp 2 )/C(sp 3 ) ratio will have excellent conduction properties. We observed the magnitude for the sp 2 cluster ratio of 85% for the a-Carbon on the SiO 2 specimen, as shown in Figure 5b.…”
Section: Structural Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As the carbon material consisted of a majority of sp 2 clusters and are good conductors, while the carbon material consisted of a majority of sp 3 clusters and are not good conductors [26], the samples with a larger C(sp 2 )/C(sp 3 ) ratio will have excellent conduction properties. We observed the magnitude for the sp 2 cluster ratio of 85% for the a-Carbon on the SiO 2 specimen, as shown in Figure 5b.…”
Section: Structural Analysismentioning
confidence: 99%
“…Subsequently, we have recently performed a series of experiments, in which we have reported on a-Carbon structure-dependent MR properties, and we reported an enhanced angular MR of 18% and negative MR of 13% for a-Carbon thin films fabricated through a CVD technique. Furthermore the mechanism of such MR properties was investigated and it was found that they greatly depend on grain boundary scattering (GBS) and weak localization theory (WLT) [25,26]. Furthermore, the correlation of MR of a-Carbon with spintronics, has greatly demanded attention in recent years owing to its magnetoresistance applications; for higher magnetic fields, a-Carbon MR is still considered as unsaturated.…”
Section: Introductionmentioning
confidence: 99%